Care pathways and treatment patterns for patients with heart failure in China: results from a cross-sectional survey - Jackson JDS; Cotton SE; Bruce Wirta S; Proenca CC; Zhang M; Lahoz R; Balas B; Calado FJ (Dove Medical Press, 2018)
James DS Jackson,1 Sarah E Cotton,1 Sara Bruce Wirta,2 Catia C Proenca,3 Milun Zhang,4 Raquel Lahoz,5 Bogdan Balas,5 Frederico J Calado5 1Real World Research, Adelphi Real World, Bollington, UK; 2Real World Evidence, Cardio-Metabolic Franchise, Novartis Sweden AB, Stockholm, Sweden; 3Wellmera AG, Basel, Switzerland; 4Health Economics and Outcomes Research, Novartis Pharma China, Beijing, China; 5Medical Affairs, Cardio-Metabolic Franchise, Novartis Pharma AG, Basel, Switzerland Purpose: The objective of this study was to describe the clinical care pathways, management and treatment patterns, and hospitalizations for patients with heart failure (HF) in China. Subjects and methods: A cross-sectional survey of cardiologists and their patients with HF was conducted. Patient record forms were completed by 150 cardiologists for 10 consecutive patients. Patients for whom a patient record form was completed were invited to complete a patient self-completion questionnaire. Results: Most of the 1,500 patients (mean [SD] age 66 [10] years; 55% male) included in the study received care in tier-2 and -3 hospitals in large cities. Cardiologists were responsible for initial consultation, diagnosis, and treatment of patients with HF. The use of guideline-recommended diagnostics was high. However, guideline-recommended double- and triple-combination therapy was received by only 51% and 18% of patients, respectively. In total, 20% of patients with HF reported that they were not consulted on the choice of therapy. Concordance was high (≥80%) between matched cardiologist and patient pairs for the occurrence of side effects, while cardiologists more often under- than overreported the occurrence of side effects of treatment reported by patients. Conclusion: The management of HF was predominantly overseen by cardiologists. The use of diagnostic tests was high, but the use of guideline-recommended treatment was low in this population. Improved communication between patients and cardiologists is essential to optimize treatment decision making and to increase awareness of treatment side effects. Keywords: heart failure, disease management, patient preference, treatment satisfaction, real-world evidence